ANALISIS HOTS PADA INSTRUMEN EVALUASI SISWA KELAS V SD N 3 KRASAK PECANGAAN JEPARA TAHUN PELAJARAN 2019/2020 - Mubin, Miftachul; Wijayanti, Arfilia; Ardiyanto, Asep (Universitas Sarjanawiyata Tamansiswa, 2021)
The purpose of the research to know the application of HOTS on SD N 3 Krasak Pecangaan Jepara. The research’s method is descriptive qualitatively. The object being analyzed are the midterms assessment (PTS) and the final assessment (PAS) the study subject is a 5th class teacher and principal of SD N 3 Krasak. Data in this research is obtained by observation and interviews. The result of this research shows that both the question of multiple-choice tests and essay in SDN 3 Krasak has contained HOTS at 33,13% percentage. The suggestion of researchers is the school needs to improve the hots skills on the instruments of evaluation so that students can think creatively.